The impact of strategy, emotional intelligence, innovation, and cross-functional teams on operational effectiveness (2021)
Organizations in this day and age are adamant to create a competitive advantage over other firms, by improving their operational effectiveness through innovation and human capital strategies like cross functional teams. It is, therefore, crucial to evaluate how Emotional Intelligence and Cross-functional teams are relevant to improve Process innovation and operational effectiveness in Colombian companies for an advantage in a globalized market. This paper analyzes quantitative data from 180 questionnaires using a structural equation model. The questionnaire was made to several industries in Colombia. Initial findings suggest that strategy implementation in the companies has a relevant impact on Cross-functional teams, emotional intelligence, and process innovation, however, it lacks to impact operational effectiveness in quality. Although emotional intelligence and strategies are deficient to create quality in operational effectiveness, Cross-functional teams presented a positive correlation with operational effectiveness, as an important variable for Colombian competitive advantage.